2022
DOI: 10.1093/icesjms/fsac073
|View full text |Cite
|
Sign up to set email alerts
|

Increases of opportunistic species in response to ecosystem change: the case of the Baltic Sea three-spined stickleback

Abstract: Under rapid environmental change, opportunistic species may exhibit dramatic increases in response to the altered conditions, and can in turn have large impacts on the ecosystem. One such species is the three-spined stickleback (Gasterosteus aculeatus), which has shown substantial increases in several aquatic systems in recent decades. Here, we review the population development of the stickleback in the Baltic Sea, a large brackish water ecosystem subject to rapid environmental change. Current evidence points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 108 publications
2
19
0
1
Order By: Relevance
“…For example, sticklebacks from turbid environments have been shown to discriminate among stickleback populations based on olfactory cues (Hiermes et al, 2015) whereas benthic sticklebacks used olfaction to discriminate between con-and heterospecific potential mates (Rafferty and Boughman, 2006), while the same ability was not found in sticklebacks inhabiting habitats with higher visibility (Mobley et al, 2016). This could potentially explain why we did not detect any general effect of treatment since the Baltic Sea sticklebacks spend a majority of their life-cycle in the offshore pelagic habitat with generally high visibility and may thus predominantly rely on visual cues (Olin et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, sticklebacks from turbid environments have been shown to discriminate among stickleback populations based on olfactory cues (Hiermes et al, 2015) whereas benthic sticklebacks used olfaction to discriminate between con-and heterospecific potential mates (Rafferty and Boughman, 2006), while the same ability was not found in sticklebacks inhabiting habitats with higher visibility (Mobley et al, 2016). This could potentially explain why we did not detect any general effect of treatment since the Baltic Sea sticklebacks spend a majority of their life-cycle in the offshore pelagic habitat with generally high visibility and may thus predominantly rely on visual cues (Olin et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
“…Multiple reasons have been linked to the decline, among them habitat degradation (Sundblad and Bergström, 2014), fisheries (Bergström et al, 2019), eutrophication (Bergström et al, 2016;Lehtonen et al, 2009), and increased predation pressure by seals (Halichoerus grypus) (Bergström et al, 2022;Hansson et al, 2018) and cormorants (Phalacrocorax carbo sinensis) (Heikinheimo et al, 2021;Östman et al, 2012). Recently, there has also been increasing support to the hypothesis that rapidly increasing abundances of the three-spined stickleback (Gasterosteus aculeatus, hereafter stickleback) negatively impact the abundances of pike and perch, which in sub-adult and adult life-stages are main predators on sticklebacks in the coastal habitat, both by resource competition and direct predation on their young (Bergström et al, 2015;Eklöf et al, 2020;Nilsson et al, 2019;Olin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, as the availability of alternative prey for cormorants has been shown to affect predation risk for juvenile salmonids (Good et al, 2022), differences in availability of alternative prey between the two time periods may have contributed to the difference. For example, in 2005-2006 it was generally more herring (a common prey in the diet of cormorants; Boström et al, 2012;Östman et al, 2013) in the area than in 2017-2021 (Olin et al, 2022). As herring assemble in coastal areas for spawning during the same time of the year as salmonids migrate to the sea (late spring-early summer), cormorants may have assembled to forage in areas with large schools of herring to a larger extent in 2005-2006 than during the most recent years (2017)(2018)(2019)(2020)(2021).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few reports have investigated sticklebacks invading the pelagic zone and interacting with other pelagic fish or zooplankton. The exception is the Baltic Sea, where numerous studies tried to reveal the causes and consequences of stickleback increase (Olin et al 2022). One study showed that sticklebacks are potential competitors for herring and sprat due to similar diets and prey selection (Jakubavičiute et al 2016), whereas others showed that sticklebacks suppress native fish by preying on their larvae (Ljunggren et al 2010;Byström et al 2015;Eklöf et al 2020).…”
Section: The Effects Of Sticklebacks On Zooplankton and Planktivorous...mentioning
confidence: 99%